Psychometric properties of the Life Skills Test in a sample of young mexicans - Santana Campas, Marco Antonio (2018)
The aim of the present study was the adaptation and evaluation of the psychometric properties of the life skills test in young Mexicans. Sample, 275 young students of upper secondary education and undergraduate degree, 43.6% of the Centro Universitario del Sur, 37.8% Centro Universitario de los Valles, and 18.5% of upper secondary education of the University of Guadalajara of the state of Jalisco, México. The 30.5 males and 69.5% women, the range between 16 and 29 years, ME 20 and 2.39. As for the occupation, 90.9% referred to be a student, 8.7% studied and worked and. 4% studied and home. Instrument: Life skills Test. Results. They demonstrate that the life skills test has adequate psychometric properties in this population, so it is an appropriate instrument to measure life skills in young Mexicans.